2016
DOI: 10.1016/j.atherosclerosis.2016.09.016
|View full text |Cite
|
Sign up to set email alerts
|

Plasma cystatin C and neutrophil gelatinase-associated lipocalin in relation to coronary atherosclerosis on intravascular ultrasound and cardiovascular outcome: Impact of kidney function (ATHEROREMO-IVUS study)

Abstract: Mild-to-moderate kidney dysfunction modifies the relationship between CysC and high-risk coronary lesions. This has not been established before, and offers an explanation for the difference in findings between experimental and epidemiologic studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 34 publications
0
8
0
2
Order By: Relevance
“…In our previous reports on the ATHEROREMO-IVUS study [ 8 12 ], levels of CRP, ferritin, RANTES, TNF-α, IL-10, cystatin C, and NGAL were associated with IVUS-VH-derived plaque burden in the full cohort. Additionally, IL-10, cystatin C, and NGAL were associated with IVUS-VH-derived thin-cap fibroatheroma (VH-TCFA) lesions.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…In our previous reports on the ATHEROREMO-IVUS study [ 8 12 ], levels of CRP, ferritin, RANTES, TNF-α, IL-10, cystatin C, and NGAL were associated with IVUS-VH-derived plaque burden in the full cohort. Additionally, IL-10, cystatin C, and NGAL were associated with IVUS-VH-derived thin-cap fibroatheroma (VH-TCFA) lesions.…”
Section: Discussionmentioning
confidence: 83%
“…This study design was chosen based on the hypothesis that such a non-stenotic segment reflects coronary wall pathophysiology in the larger coronary tree [ 13 •]. This assumption, on its part, was based on the fact that ex vivo, as well as in vivo, studies in patients with myocardial infarction, have demonstrated presence of TCFA (as assessed by IVUS) located elsewhere than the culprit lesion or even culprit artery [ 8 12 ]. In fact, we were subsequently able to confirm this hypothesis, by demonstrating that NIRS imaging characteristics of the non-culprit artery are associated with increased risk of MACE [ 6 ••].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cystatin C je přirozeně produkován také kardiomyocyty, jeho produkce vzrůstá v závislosti na působení ischemie, hypoxie a oxidačním stresu [2,11,15]. Díky ovlivnění proteázové aktivity má cystatin C také úlohu v regulaci zánětlivé odpovědi, procesu aterogeneze a destabilizaci ateromového plátu [10,13,15,16].…”
Section: Diskuseunclassified
“…However, even if they are on optimal therapy they will still have poorer prognosis [7]. Renal dysfunction is associated with coronary atherosclerosis, including higher coronary plaque burden, plaques containing greater necrotic core and more dense calcium, as well as with abnormalities of cardiac muscle, including left ventricular hypertrophy, dilated cardiomyopathy, and systolic dysfunction [8][9][10]. Several studies have shown that specific comorbidities such as hypertension, diabetes, and dyslipidemia, contribute both to cardiovascular and renal damage [11,12].…”
Section: Introductionmentioning
confidence: 99%